Clinical management of the adult patient with dental anxiety - Tvermyr, Kathrine; Hoem, Anna Frydendal; Elde, Kine Marlén (Universitetet i Tromsø, 2012)
Abstract Background: Dental anxiety is a prevalent issue which every dental practitioner will face. As dental anxiety involves personal consequences for the affected patients - as well as hampering the clinical performance of the dental profession – this matter should be taken seriously and dealt with accordingly. The treatment of dental anxiety thus should be within the competence of the general practitioner. Aims: To systematically review the literature concerning treatment of adult fearful and anxious patients, in order to find strategies to empower both patient and dentist in the clinical situation. Our hypothesis is that there are measures a general dentist can take to ease the dental treatment of fearful patients. Our goal is to present the general dentist approaches regarding identification and care of these patients. Material and methods: Systematic search of the literature was performed via Pubmed and using Google search engine. We used search terms such as: “dental anxiety”, “fearful dental patients”, “etiology of dental fear” and “adult fearful patients.” The primary selection of articles, books and doctoral theses was based on their title abstract, and time of publication. The inclusion criteria were Scandinavian and English publications presenting knowledge about etiology, prevalence and clinical management of dental anxiety in adults. We also performed interviews with anxious patients at the TkNN (Tannhelsetjenestens kompetansesenter for Nord-Norge). Conclusions: Identifying anxious dental patients can be achieved by the use of a semi-structured interview and/or through psychometric questionnaires, such as Dental Anxiety Scale (DAS), Dental Belief Survey (DBS) and Dental Fear Survey (DFS). There are both general and specific approaches to treating dental anxiety, as well as pharmacological aids. The method of choice should be adapted to the patient’s prerequisites and individual needs. Even though much can be accomplished by the general dentist, some patients may have very complex and comprehensive ...